“Women live at the mercy of men”- undergraduate students’ responses to gender in Jane Austen’s Pride and Prejudice and contemporary Pakistani society - Lashari, Asadullah; Shaikh, Ghazal; Shaikh, Tania (University of Chitral Journal of Linguistics and Literature, 2024)
The study explored the perceptions of undergraduate students at a public university in Pakistan, regarding the issues of gender, marriage and social class identity in relation to Austen’s novel Pride and Prejudice. The study was guided by Rosenblatt's Transactional Reader Response Theory that views the reader and the text as partners and active agents in the meaning-making process. The data collected through 23 written scripts of students was analysed using thematic analysis. The findings suggested that students identified the themes of gender, marriage and social class identity in the novel and related to the present day issues of Pakistani society. Moreover, students’ responses validate Rosenblatt’s transactional model that they not only took meaning from the text in understanding 19th century English life but also assigned meaning to the text by interpreting the text in light of their own experiences of 21st century Pakistani society.